A Comparison of the Translation of the Arabic Text in the Mu'allaqat Between Artificial Intelligence and Human Translation - Renny Dwi Arumsari; Vira Hilma Fadhila; Niken Salindri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
This study explores the role of Artificial Intelligence (AI), specifically ChatGPT, in translating classical Arabic literary texts, focusing on Mu’allaqat by Imru’ al-Qais. Using a qualitative descriptive method with a comparative approach, the research compares AI-generated translations with expert-validated manual interpretations. Ten poetic verses were evaluated using a rubric assessing accuracy, clarity, naturalness, and consistency. The findings reveal that ChatGPT generally produces translations categorized as good, especially in clarity and language flow. However, some weaknesses were found in preserving exact meanings and consistent use of terms, particularly in verses with deep emotional and cultural layers. State the implications of the research findings for the development of translation theory. Explain how the findings can strengthen, support, or provide a new perspective on the theory employed. If possible, also describe the contribution of these findings to future research.